Impact of dietary intervention on eating behavior after ischemic stroke - Besseau, Samuel; Sartori, Eric; Larnier, Pauline; Paillard, François; Laviolle, Bruno; Mahé, Guillaume (Frontiers in Nutrition, 2023)
Objective: In France, approximately 100,000 patients are hospitalized every year for a stroke among which 85 % are ischemic. Today the link between dietary pattern and the occurrence of cardiovascular diseases including stroke is established. But a systematic dietary intervention on dietary changes in ischemic stroke patients is unknown. Our objective was to compare dietary pattern changes of ischemic patients with a systematic diet intervention with dietary patterns changes of ischemic patients without a systematic dietary intervention. Methods: Two groups of patients with stroke were compared in a non-randomized observational study. Group 1 included 34 patients admitted with an ischemic stroke without a systematic intervention. Group 2 included 34 patients admitted with an ischemic stroke with a systematic dietary consultation. Dietary patterns were assessed by food frequency questionnaire of 19 questions (from a previous validated questionnaire of 14 questions) in the onset of stroke and after 6 months. This questionnaire allows the calculation of different scores: global food score, saturated fatty acids score (SFA), unsaturated fatty acids score (UFA), fruits/vegetables score and alcohol score. Results: Score changes were more important in group 2 than in group 1 for the global food score (7.4 ± 7 vs 1.9 ± 6.7, p = 0.0013), fruits/vegetables score (2 ± 2.6 vs 0.6 ± 2.2, p = 0.0047) and UFA score (1.8 ± 2.7 vs 0.1 ± 3,3, p = 0.0238) whereas no significant differences were found for SFA score (-3.9 ± 4.9 vs -1.6 ± 6, p = 0.1779) and alcohol score (-0.4 ± 1.5 vs -0.3 ± 1.1, p = 0.6960). Conclusion: This study showed, that systematic dietary intervention improves dietary pattern of patients after ischemic stroke. Impact on recurrence of ischemic stroke or cardiovascular events after dietary pattern changes needs to be studied.